1965
DOI: 10.1017/s0022143000018906
|View full text |Cite
|
Sign up to set email alerts
|

On the Relationship of Snow Accumulation to Surface Topography at “Byrd Station”, Antarctica

Abstract: ABSTRACT. R ecent measurements of snow acc umulation on undulat ing surfaces around " Byrd station " , Antarctica indicate that the undulations a re tending to be filled in. These resu lts are discussed in the lig ht of c urrent knowledge of the or igin and migration of such features.RESU ME. Relalion mire I' accwnulalion de la "eige el la lopographie sllperjicielle cl la statioll " By rd" , Anlarctique. D e recentes m esures d' accumu lation de la neige sur la surface ondu lee a utour de la station " Byrd", i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
0

Year Published

1982
1982
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(38 citation statements)
references
References 3 publications
4
34
0
Order By: Relevance
“…Variations in snow layer thickness were observed in association with topographic features, which suggest that wind redistribution have a major influence on the local accumulation pattern. This relation has also been recognized in several previous studies, such as Black and Budd [1964] and Gow and Rowland [1965]. The considerable spatial variability in snow accumulation observed indicates that the accumulation pattern is complex and that broad-scale Antarctic snow accumulation is difficult to describe by parameterization of air [1990], who found that they were able to make reliable parameterizations only for the ice sheet interior.…”
Section: Discussionsupporting
confidence: 71%
“…Variations in snow layer thickness were observed in association with topographic features, which suggest that wind redistribution have a major influence on the local accumulation pattern. This relation has also been recognized in several previous studies, such as Black and Budd [1964] and Gow and Rowland [1965]. The considerable spatial variability in snow accumulation observed indicates that the accumulation pattern is complex and that broad-scale Antarctic snow accumulation is difficult to describe by parameterization of air [1990], who found that they were able to make reliable parameterizations only for the ice sheet interior.…”
Section: Discussionsupporting
confidence: 71%
“…The dune crests are oriented orthogonally to the wind direction, while the sastrugi are oriented parallel to the wind direction. They become more level during the summer by sublimation and deflation [16], [17]. Albert and Hawley [3] showed that surface roughness heights are less than 8 cm from late June to later December but started to increase around January.…”
Section: B Temporal Variation Of Dry-snow Zone 1) Summit Sitementioning
confidence: 99%
“…Relationships between the spatial variations in snow accumulation and the katabatic outflow have long been recognized (Gow and Rowland, 1965) and have been further elucidated by ground-probing radar profiles and firn cores, but they are still poorly understood (Melvold and others, 1998), particularly on an event-by-event basis. Consequently, a more detailed quantitative understanding of the spatio-temporal aspects of accumulation is desirable.…”
Section: Introductionmentioning
confidence: 99%